Influence of native language on Nasalance values in Kannada and Malayalam speakers - K S Girish; M Pushpavathi; H V Satish (Wolters Kluwer Medknow Publications, 2021)
Introduction: Nasalance values vary across languages. Therefore, establishing separate normative values of nasalance for each language and studying their influence on each other becomes important for the assessment and management of persons with resonance disorders. So the present study aimed at comparing the nasalance values of vowels, unvoiced syllables, and voiced syllables between native Kannada speakers and native Malayalam speakers. The present study also compared the nasalance values of meaningful words, oral sentences, and nasal sentences (for both English and Kannada languages) between native Kannada speakers and native Malayalam speakers. Materials and Methods: Twelve native Kannada speakers and 12 native Malayalam speakers (age range - 18-23 years) served as participants. The test stimuli included a standardized set of meaningful words, oral sentences, and nasal sentences in both English and Kannada, vowels, unvoiced syllables, and voiced syllables. The data were recorded and the values were obtained from the Nasometer. Results: The results revealed a higher nasalance value for Malayalam speakers (/a/-29,i/-45.41,u/-19.50, unvoiced syllables-16.96, voiced syllables-21.63, words-22.71, oral sentences-21.40, and nasal sentences-60.15) than for Kannada speakers (/a/-14.90,i/-32.60,u/-10.50, unvoiced syllables-11.59, voiced syllables-16.99, words-15.83, oral sentences-13.62, and nasal sentences-56.18) across all the stimuli considered. However, a statistically significant difference was found only on vowels. Conclusions: The present study indicated that in bilingual or trilingual speakers, there is an effect of native language on the Nasalance Values of second and/or third language.